Dietary Patterns and Breast-Feeding in Australian Children - Grieger, J.; Scott, Jane; Cobiac, L. (Cambridge University Press, 2011)
Objective: To determine the dietary patterns of a national sample of 2–8-year-old Australian children and to establish whether breast-feeding is associated with dietary patterns in this age group.Design: Cross-sectional study using 24 h recall data from the 2007 Australian National Children’s Nutrition and Physical Activity Survey.Setting: Australia.Subjects: A total of 2287 children aged 2–8 years.Results: Principal component factor analysis identified three distinct patterns. The ‘Non-core food groups’ pattern included food groups such as whole-fat dairy products, cheese, medium–high sugar-sweetened breakfast cereals and sweet biscuits, no fruit, reduced/low-fat dairy products and wholegrain bread/rolls. The ‘Healthy, meat and vegetable’ pattern included vegetables, red meat, fruit and wholegrain bread/rolls and was inversely associated with take-away foods and carbonated sugar-sweetened beverages. The ‘Combination’ pattern contained many food groups including candy (not chocolate based), pasta/rice products, nuts/seeds, cakes and chocolate, but no fruit or vegetables. Of the 2287 children, 2064 (89.3%) had been breast-fed. A positive association was found betweenbreast-feeding and the healthy, meat and vegetable pattern (r=0.267) but not with the other two patterns. Higher scores on this pattern were also associated with younger age, lower BMI, higher birth weight, high likelihood of being in the less-disadvantaged Socio-economic Indexes for Areas category and less likelihood of the child’s parents having a lower educational level.Conclusions: These results provide suggestive evidence that breast-feeding during infancy is associated with a healthy dietary pattern in childhood and offers a likely pathway to explain the previously reported association between breast-feeding and chronic disease.